PRODUCTION AND CHARACTERIZATION OF BIO CATALYTIC ENZYME PRODUCED FROM FERMENTATION OF FRUIT AND VEGETABLE WASTES AND ITS INFLUENCE ON AQUACULTURE SLUDGE - Rasit, Nazaitulshila; Mohammad, Fatma Syahirah (MATTER: International Journal of Science and Technology, 2018)
The aquaculture sludge discharged from shrimp aquaculture industry may result in high organic content and nutrients that are considered as a source of surface and ground pollution. Hence, before disposing, it has to be treated efficiently to reduce its pollutants concentration. Anaerobic digestion technology has been commonly applied for sludge treatment but it requires longer retention time and the efficiency for the overall organic matter degradation is relatively low. Therefore, a pretreatment is usually applied before further anaerobic treatment. This study focused on the production of bio catalytic enzyme from fermentation of fruit and vegetable wastes such as pineapple, mango, orange and tomato dregs to increase the aquaculture sludge stability. The solution of the wastes is known as garbage enzyme. It was produced by three months’ fermentation of molasses, waste and water mixture with the ratio of 1:3:10. Characterization of the enzyme showed that it possessed lipase, amylase and protease activities. All types of fruit and vegetable wastes were pretreated individually at pH 7.0 within the duration of 120 hours and were labelled as pineapple garbage enzyme (PGE), mango garbage enzyme (MGE), orange garbage enzyme (OGE) and tomato garbage enzyme (TGE). The efficiency of the pretreatment was evaluated based on the removal of total suspended solid (TSS), volatile suspended solid (VSS), chemical oxygen demand (COD) and total ammonia nitrogen (TAN). A higher removal of all parameters was observed in all pretreated experiments. The pineapple garbage enzyme performed a greater reduction of TSS and VSS within the range of 54 percent to 72 percent. COD removal efficiency was higher in pineapple and orang garbage enzyme with 82 percent and 88 percent removal, respectively. While for TAN, orange garbage enzyme showed a higher reduction with 65 percent removal. These findings proved that enzyme solution produced from fruit and vegetable wastes have the potential to pretreat aquaculture sludge when the reduction of selected parameters were observed and this will help reducing shock lock or inhibition prior to anaerobic digestion.